Unraveling the evidence on occupational therapy in the hospital context: integrative review (Research, Society and Development, 2022)
This study aimed to raise the results of scientific productions that refer to the work of Occupational Therapists in Hospital Context in Brazil, in the face of similar areas of Hospital Contexts. It is an integrative review with a qualitative approach. Full articles published in Brazilian Occupational Therapy journals were included in this study. As a research strategy, the search with descriptors “Hospital Day”, “Hospitalization” and “Hospital Contexts” was used. A total of 49 articles were found. After classifying them, seven groups were created, arranged in areas related to the Hospital Context. It was found that the areas that are in greater ascendancy in this context are Occupational Therapy in functional health and in childhood. The areas of Occupational Therapy in Thanatology and Occupational Health showed no evidence in the period studied. In most of the published articles, the discourse of valuing professional practice is evident. The occupational therapist, since his initial training, must understand the importance of scientific production, of approaching his clinical reasoning and carrying out his practices through evidence-based practice, and this practice will only be possible if professionals contribute to the collection of studies of this profession. which is on the ascendancy.